Revision and phylogeny of Chelagyrtodes Szymczakowski (Coleoptera: Leiodidae: Camiarinae: Agyrtodini) - Seago, Ainsley E.; Leschen, Richard A. B. (Zootaxa, 2011)
The formerly monotypic New Zealand leiodid genus Chelagyrtodes Szymczakowski (type species Chelagyrtodes crowsoni Szymczakowski) is revised to include five new species from the South Island: C. newtoni n. sp., C. rotundus n. sp., C. haasti n. sp., C. glacicola n. sp., and C. davidi n. sp. Four of these new species lack the unusual tibial dimorphism previously used to diagnose this genus, but can be recognized by the presence of a subapical spine cluster on the interior face of the mandible, procoxal cavities with an anterior carina or bead, and a series of minute, setiferous punctures along the lateral margins of the hypomeron. A key and phylogenetic analysis based on adult morphology is provided for the six species of Chelagyrtodes. Natural history and distribution of Chelagyrtodes are discussed in the context of phylogenetic data.